The exercise pressor reflex and chemoreflex interaction: cardiovascular implications for the exercising human - Wan, Hsuan‐Yu; Weavil, Joshua C.; Thurston, Taylor S.; Georgescu, Vincent P.; Hureau, Thomas J.; Bledsoe, Amber D.; Buys, Michael J.; Jessop, Jacob E.; Richardson, Russell S.; Amann, Markus (The Journal of physiology, 2020)
Key points Although the exercise pressor reflex (EPR) and the chemoreflex (CR) are recognized for their sympathoexcitatory effect, the cardiovascular implication of their interaction remains elusive. We quantified the individual and interactive cardiovascular consequences of these reflexes during exercise and revealed various modes of interaction. The EPR and hypoxia‐induced CR interaction is hyper‐additive for blood pressure and heart rate (responses during co‐activation of the two reflexes are greater than the summation of the responses evoked by each reflex) and hypo‐additive for peripheral haemodynamics (responses during co‐activation of the reflexes are smaller than the summated responses). The EPR and hypercapnia‐induced CR interaction results in a simple addition of the individual responses to each reflex (i.e. additive interaction). Collectively, EPR:CR co‐activation results in significant cardiovascular interactions with restriction in peripheral haemodynamics, resulting from the EPR:CR interaction in hypoxia, likely having the most crucial impact on the functional capacity of an exercising human. We investigated the interactive effect of the exercise pressor reflex (EPR) and the chemoreflex (CR) on the cardiovascular response to exercise. Eleven healthy participants (5 females) completed a total of six bouts of single‐leg knee‐extension exercise (60% peak work rate, 4 min each) either with or without lumbar intrathecal fentanyl to attenuate group III/IV afferent feedback from lower limbs to modify the EPR, while breathing either ambient air, normocapnic hypoxia (SaO2 ∼79%, PaO2 ∼43 mmHg, PaCO2 ∼33 mmHg, pH ∼7.39), or normoxic hypercapnia (SaO2 ∼98%, PaO2 ∼105 mmHg, PaCO2 ∼50 mmHg, pH ∼7.26) to modify the CR. During co‐activation of the EPR and the hypoxia‐induced CR (O2‐CR), mean arterial pressure and heart rate were significantly greater, whereas leg blood flow and leg vascular conductance were significantly lower than the summation of the responses evoked by each reflex alone. During co‐activation of the EPR and the hypercapnia‐induced CR (CO2‐CR), the haemodynamic responses were not different from the summated responses to each reflex response alone (P ≥ 0.1). Therefore, while the interaction resulting from the EPR:O2‐CR co‐activation is hyper‐additive for blood pressure and heart rate, and hypo‐additive for peripheral haemodynamics, the interaction resulting from the EPR:CO2‐CR co‐activation is simply additive for all cardiovascular parameters. Thus, EPR:CR co‐activation results in significant interactions between cardiovascular reflexes, with the impact differing when the CR activation is achieved by hypoxia or hypercapnia. Since the EPR:CR co‐activation with hypoxia potentiates the pressor response and restricts blood flow to contracting muscles, this interaction entails the most functional impact on an exercising human. Key points Although the exercise pressor reflex (EPR) and the chemoreflex (CR) are recognized for their sympathoexcitatory effect, the cardiovascular implication of their interaction remains elusive. We quantified the individual and interactive cardiovascular consequences of these reflexes during exercise and revealed various modes of interaction. The EPR and hypoxia‐induced CR interaction is hyper‐additive for blood pressure and heart rate (responses during co‐activation of the two reflexes are greater than the summation of the responses evoked by each reflex) and hypo‐additive for peripheral haemodynamics (responses during co‐activation of the reflexes are smaller than the summated responses). The EPR and hypercapnia‐induced CR interaction results in a simple addition of the individual responses to each reflex (i.e. additive interaction). Collectively, EPR:CR co‐activation results in significant cardiovascular interactions with restriction in peripheral haemodynamics, resulting from the EPR:CR interaction in hypoxia, likely having the most crucial impact on the functional capacity of an exercising human.